PENGARUH SOCIAL INFLUENCE DAN PERSONAL INNOVATIVENESS TERHADAP PERCEIVED USEFULNESS MELALUI BEHAVIORAL INTENTION PENGGUNA TRAVELOKA (STUDI KASUS: PADA MAHASISWA UST YOGYAKARTA) - Roki Satria Jaya; IB Nyoman Udayana; Putri Dwi Cahyani (Buletin Ekonomi: Manajemen, Ekonomi Pembangunan, Akuntansi, 2020)
This study aims to examine the influence of Social Influence, Personal Innovation on Perceived Usefulnes Through Behavioral Intention. The research was conducted as many as 100 respondents Traveloka users at Sarjanawiyata Tamansiswa University Yogyakarta Students. The results of this study indicate: 1) Social Influence has a positive and significant effect on Perceived Usefulness 2) Personal Innovativeness has a positive and significant effect on Perceived Usefulness 3) Perceived Usefulness has a positive and significant effect on Behavioral Intention 4) Social Influence has a positive and significant effect on Behavioral Intention 5) Personal Innovativeness has a positive and significant effect on Behavioral Intention.Penelitian ini bertujuan untuk menguji pengaruh Social Influence, Personal Innovation terhadap Perceived Usefulnes Through Behavioral Intention. Penelitian ini dilakukan sebanyak 100 responden pengguna Traveloka pada Mahasiswa Universitas Sarjanawiyata Tamansiswa Yogyakarta. Hasil penelitian ini menunjukkan: 1) Social Influence berpengaruh positif dan signifikan terhadap Perceived Usefulness 2) Personal Innovativeness berpengaruh positif dan signifikan terhadap Perceived Usefulness 3) Perceived Usefulness berpengaruh positif dan signifikan terhadap Behavioral Intention 4) Social Influence memiliki pengaruh positif dan signifikan terhadap Behavioral Intention 5) Personal Innovativeness berpengaruh positif dan signifikan terhadap Behavioral Intention.